Foreign agent [compact disc, unabridged] : a thriller - Thor, Brad (Thor, Brad. Scot Harvath., 2016)
In a safe house near the Syrian border, a clandestine American operations team readies to launch a dramatic mission months in the making. Their target: the director of Social Media for ISIS, Abu Muslim al-Naser. Loaded with action, this globetrotting, pulse-pounding thriller masterfully weaves espionage and counterterrorism into a captivating adventure.